Maqasid Qs. Al-Fiil: Koneksitas Munasabah dan Al-Kulliyat Al-Khams - Aljuraimy Aljuraimy; A. Halil Thahir (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2019)
This article discusses the mashlahat hold to al-kulliyat al-khams and munasabah in the verses of surah Al-Fil. Al-kulliyat al-khams is a product of ushul fiqh that upholds the preservation of maslahah in every level of need. The writer relates it to the science of interpretation and attempts to adopt it so as not to focus only on legal matters. The adobtion argued the existence of aspects of religion, soul, mind, descent and property, those must be maintained for the mashlahah, benefit, of the world and the hereafter. As the concept of interconnection of maslahah, these five aspects are interrelated. The aspect of religion as a top priority in this case, aims as a standard of value for other aspects. Because as al-Ghazali stated that the aim of the Shari'a was to maintain the goal of Shara ', so it is not logical if the aspect of religion would harm other aspects. Maqasid al-Suwar from surah Al-Fil is a prohibition on hasad. Whereas the connectivity of maslahah among verses in the surah is as follows. 1) Religion : hasad is a characteristic that is prohibited in Islam, being protected from this nature fulfills the aspects of morals. 2) Soul and 3) mind : a person who has a hasad character, is psychologically unstable, because he will be obsessed with eliminating the pleasures of others, so that he is awake of hasadish nature maintains the stability of soul and mind, and 4) descent and 5) property: a person who has a willful nature will be greedy with the possessions of others, so instead of being grateful or maintaining his own, but trying to look superior to others.